INCONGRUENT EVAPORATION OF TROILITE (FES) IN THE PRIMORDIAL SOLAR NEBULA: AN EXPERIMENTAL STUDY - Tachibana S.; Tsuchiyama A. (My University, 1998)
Incongruent evaporation experiments on troilite (FeS) were carried out under H2-rich conditions at total pressure 1.0-10-6 atm (800-970°C) to elucidate the kinetics of incongruent evaporation of troilite in the primordial solar nebula. Sulfur evaporates from troilite linearly with time, and a porous residual layer of metallic iron is formed. It was concluded from the results and consideration on individual possible processes during the evaporation that the evaporation rate of sulfur is controlled by the surface chemical reaction. The evaporation rate at 1 atm total pressure depends largely on hydrogen pressure, p(H2), while that under low p(H2) conditions has a little dependence on p(H2). These results indicate that sulfur evaporates from troilite mainly as H2S under high p(H2) conditions, while mainly as S2 (and HS) under low p(H2) conditions. The evaporation coefficients, α, which represent the degree of kinetic constrains of evaporation, were obtained from the experimental results and thermodynamic calculations: αH2S = 2.03 x 10-3 p(H2)0.106 exp(-940/T), αHS = 1.94 x 10-2 p(H2)-0.136 exp(-2040/T), and αS2 = 0.922 exp(-2220/T). Small values of α for evaporation as H2S (<0.001) may be due to a sluggish surface reaction between H2 molecules and troilite. This causes the metastable reaction including S2 under low p(H2) conditions.Taking the present results and p-T conditions in the primordial solar nebula into consideration, it was concluded that troilite would evaporate incongruently as H2S in low temperature regions of the outer primordial solar nebula and as S2 (and HS) in high temperature regions. Since residual metallic iron evaporates little, the incongruent evaporation of troilite can cause the Fe/S fractionation in the primordial solar nebula.